Membran Spermatozoa Hasil Seksing Gradien Albumin Berpengencer Andromed dan Cauda Epididymal Plasma-2 Ditambahkan Kuning Telur (MEMBRANE OF SPERM FOLLOWING GRADIENT ALBUMIN SEXING USING ANDROMED AND CEP-2 SUPPLEMENTED WITH EGG YOLK) - Purwoistri, Rita Fitria; Susilawati, Trinil; Rahayu, Sri (Jurnal Veteriner, 2013)
The objective of this study was to determine sperm membrane stability after sexing with gradientalbumin (egg white) using andromed and CEP-2 supplemented with 10% egg yolk. The observations ofsperm membrane included membrane integrity, uncapacitated, capacitated  and acrosome reacted. Albumingradient was made by mixing egg white with andromed or CEP-2 supplemented with 10% egg yolk resultingin a concentration of egg whites 10%, 30% and 50%. Membrane integrity was observed using HOST(Hypoosmotic Swelling Test), while uncapacitated, capacitated and acrosome reacted sperm  were observedusing CTC (Chlortetracycline) staining. The results showed that both andromed and CEP-2 supplementedwith 10% egg yolk could protect membrane integrity, uncapacitated, capacitated and acrosome reactedsperm. Andromed and CEP-2 supplement with 10% egg yolk could reduce the demage of membrane integrityand uncapacitated sperm, whereas capacitated and acrosome reacted sperm could be kept low.
Keywords: andromed, CEP-2, sperm membrane, sexing